2015
DOI: 10.1080/02755947.2015.1052160
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Avoidance Characteristics of Prenant's Schizothoracin Schizothorax prenanti to Total Dissolved Gas Supersaturated Water

Abstract: When water is allowed to spill over a hydroelectric dam, the intense aeration and pressure in the deep plunge‐pool produced by the high‐volume discharge generates water supersaturated with total dissolved gases (TDGs) in areas downstream from the dam, which can cause gas bubble disease (GBD) in fish and threaten their survival. Experiments were conducted to measure the acute lethality, intermittent exposure, horizontal avoidance, and vertical avoidance of Prenant's Schizothoracin Schizothorax prenanti related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 18 publications
4
53
1
Order By: Relevance
“…The LT 50 values of these fish were all above 15 hr at 125% TDG and exceeded 9 hr at 130% TDG. Relative studies of endemic species in the Yangtze River (e.g., rock carp, prenant's schizothoracin and silver carp) have been performed through laboratory experiments (Cao et al, ; Huang et al, ; Wang et al, ). Table shows the LT 50 values of these three species and Chinese sucker at TDG supersaturation levels of 125%, 130%, 135% and 140%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LT 50 values of these fish were all above 15 hr at 125% TDG and exceeded 9 hr at 130% TDG. Relative studies of endemic species in the Yangtze River (e.g., rock carp, prenant's schizothoracin and silver carp) have been performed through laboratory experiments (Cao et al, ; Huang et al, ; Wang et al, ). Table shows the LT 50 values of these three species and Chinese sucker at TDG supersaturation levels of 125%, 130%, 135% and 140%.…”
Section: Discussionmentioning
confidence: 99%
“…In China, fish downstream of dams die from GBD during flood discharges (Tan, Ni, Zheng, Li, & Li, ). Moreover, some laboratory experiments were carried out to assess the effect of TDG supersaturation on fish, such as rock carp ( Procypris rabaudi ), Chinese sucker, silver carp ( Hypophthalmichthys molitrix ) and prenant's schizothoracin ( Schizothorax prenanti ) (Cao, Liang, Tuo, Li, & Li, ; Chen et al, ; Huang, Li, Du, & Li, ; Wang, Li, Li, Li, & Deng, ). Liang, Li, Li, and Tuo () first investigated the relationship between hatching rate and TDG levels.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality of David's schizothoracin ( Schizothorax davidi ) fry did not exceed 50% when they were exposed to water with TDG supersaturation levels less than 125%, and their LT 50 reached 35 hr when they were exposed to waters with TDG supersaturation levels of 130% (Liang et al, ). The LT 50 of Prenant's schizothoracin ( Schizothorax prenanti ) with a weight less than 10 g was approximately 20 hr when exposed to water with a TDG supersaturation level of 120% (Wang, Li, et al, ). Moreover, Chinese suckers ( Myxocyprinus asiaticus ) with a weight of approximately 40 g could survive in water with a TDG supersaturation level of 125% for 43 hr (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Qu, Li, Li, Li, and Deng () found that outflow from the Three Gorges Dam caused the TDG supersaturation level to reach 143% and that only 17% of the supersaturated TDG had been released 600 km downstream of the dam. Previous studies have indicated that fish can be severely compromised when the TDG supersaturation level reaches 120% (Geist, Linley, Cullinan, & Deng, ; Huang, Li, Du, & Li, ; Smiley, Drawbridge, Okihiro, & Kaufmann, ; Wang, Li, Li, Li, & Deng, ; Wang, Liang, Tuo, Li, & Hodges, ). TDG supersaturation is associated with hydrostatic pressure, and when the TDG concentration in the water is constant, the supersaturation level will decrease with increasing water depth (Weitkamp, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation